Application of the selected yeast isolate in type IV sourdough to produce enriched clean-label wheat bread supplemented with fermented sprouted barley - Maryam Pahlavani; Alireza Sadeghi; Maryam Ebrahimi; Mahdi Kashaninejad; Ali Moayedi (Journal of Agriculture and Food Research, 2024)
Technological-functionalities of the yeasts isolated from fermented sprouted cereals have received much attention. In the present study, predominant yeasts were isolated from spontaneous fermented sprouted barley (FSB). Then, the isolates were screened based on their antifungal activity and their ability to enlarge the dough volume. Subsequently, the selected isolate was used as starter culture in type IV sourdough (SD) to produce enriched wheat bread. Sequencing results of the PCR products led to the identification of Wickerhamomyces anomalus as the selected yeast isolate. The produced bread containing FSB with crumb hardness of 3.56 N, specific volume of 3.44 cm3/g, and porosity of 23.13 % was identified as the most suitable sample in terms of textural features among the produced breads. The lowest amount of surface growth of Aspergillus flavus in a challenge test was also observed on wheat bread containing fermented barley, which was significantly (P < 0.05) lower than in the control sample. The highest overall acceptability was also belonged to wheat bread containing FSB. Due to the appropriate techno-functional capabilities of W. anomalus isolate, it can be used as an SD starter culture in the bakery industries.